Dosimetry for FLASH Radiotherapy: A review of dosimetric systems - Karoline Feitoza Suzart; Maria da Penha Albuquerque Potiens (Brazilian Journal of Radiation Sciences, 2025)
FLASH radiotherapy (FLASH-RT) is a promising approach to cancer treatment, characterized by the delivery of high doses of radiation in a short period of time, within fractions of seconds. In order to demonstrate the FLASH effect, single high doses of radiation delivered in very short times through a limited number of pulses are required. Previous studies have reported that FLASH-RT treatment can result in increased cell survival compared to conventional radiotherapy. This article aims to conduct a comprehensive literature search on dosimetry in FLASH radiotherapy, an emerging and promising technique in the field of radiotherapy. Some of the most used dosimeters in recent studies for FLASH radiotherapy will be discussed, including ionization chambers, diamond detectors, radiochromic films, EBT3 radiochromic films and thermoluminescent dosimeters. The main dosimetry parameters used in FLASH radiotherapy treatments will be analyzed, with emphasis on the characteristics and applicability of the different types of dosimeters used.